"I Don't Think My Landlord Will Find Out:" Airbnb and the Challenges of Enforcement. Issue 4 (2nd October 2018) - Leshinsky, Rebecca; Schatz, Laura
Abstract: Airbnb is an established part of the platform economy, which in many cities is operating unregulated. Some jurisdictions, however, have started regulating this sector, even imposing bans on short-term rentals (STR). Where regulatory limits have been instituted, local officials identify enforcement as a challenge. Amidst the dearth of enforcement resources, some local councils are turning to private companies, thereby introducing private enforcement which does not sit well in the planning (public) law context. We query whether traditional enforcement strategies can even succeed in the platform economy of STRs and whether alternatives to STR regulation make for a more realistic approach.